Arrest of ships and general average. Legal lessons from the Ever Given case - Orbegozo Miguel, Xabier (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
In March 2021, the Ever Given ran aground in the Suez Canal generating an unprecedented collapse in the main shipping route linking the Asian continent with European ports. After the initial impact, the legal interest focused in the following days on the arrest for the debt generated to the Canal authorities and on the declaration of general average by the shipowner, which was probably the largest amount for which this instrument has been used to date. This paper aims to show the main characteristics of these singular institutions of Maritime Law.